Concurrent Vitiligo and Psoriasis - Karn, D; KC, S (Kathmandu University Medical Journal, 2012)
Coexistence of vitiligo and psoriasis in a single patient is a rare occurrence. The exact pathogenesis of this coexistence is obscure. Various autoimmune disorders are reported to occur more frequently in patients with both diseases. A case of this interesting coexistence seen on a 26 year old female patient who presented to the dermatology department of Dhulikhel hospital is presented here. She also had hypothyroidism. The possible pathogenesis and literature review of this rare condition is discussed here. KATHMANDU UNIVERSITY MEDICAL JOURNAL  VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 83-84 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6921